COMBINATIONS OF Hibiscus sabdariffa WITH Zingiber officinale AND Allium sativum INHIBIT α-AMYLASE AND α-GLUCOSIDASE: A GUIDE TO DOCKING OF H. sabdariffa CONSTITUENTS - Abdulrahman-Orire, Rofiat A.; Alli, Abdulhameed O.; Salaudeen, Kafayat A.; Hassan, Rihanat I. (FUDMA Journal of Sciences, 2026)
Conventional enzyme inhibitors such as acarbose are widely used for the control of postprandial hyperglycemia by virtue of their inhibitory action on carbohydrate-hydrolyzing enzymes, but are often associated with side effects, necessitating the development of safer plant-derived alternatives. In this study, the in vitro and in silico inhibitory activities of aqueous Hibiscus sabdariffa calyx, Zingiber officinale, and Allium sativum extracts against α-amylase and α-glucosidase were investigated. H. sabdariffa (HS) calyces, Z. officinale (ZO) roots and Allium sativum (AS) bulbs were extracted using an aqueous method. For α-glucosidase inhibition, IC50 values were 39.08 µg/mL (HS), 308.91 µg/mL (ZO), 657.64 µg/mL (AS), 139.99 µg/mL (HS + AS), 73.46 µg/mL (HS + ZO), and 21.94 µg/mL (acarbose). Against α-amylase, values were 70.81 µg/mL (HS), 396.43 µg/mL (ZO), 2483.28 µg/mL (AS), 92.04 µg/mL (HS + AS), 79.76 µg/mL (HS + ZO), and 56.14 µg/mL (acarbose). In silico XP docking, acarbose had higher docking scores (-10.699 kcal/mol for α-glucosidase and -13.09 kcal/mol for α -amylase) than 3-hydroxystigmast-5-en-7-one, a HS bioactive compound which showed higher docking scores (-7.463 kcal/mol for α-glucosidase and -4.795 kcal/mol for α -amylase) compared to other HS compounds, justifying the in vitro results that revealed acarbose as the most potent inhibitor based on IC50. Although the extracts were less potent than the reference drug acarbose, their natural origin and observed synergistic action are pointers to their prospect as safer controls for postprandial hyperglycemia. Further research elucidating active compounds of HS and validating in vivo antidiabetic activity of this combined extract is recommended